Changes in the agrarian structure in Poland in the years 1921-2002 based on the example of selected provinces from three annexed territories - Michal Bernard Pietrzak; Damian Walczak (Institute of Economic Research (IER), 2013)
The objective of the paper is to analyse the agrarian structure in Poland in the years 1921-2002 based on the example of the following selected provinces from the former three annexed territories: the wielkopolskie province from the Prussian partition, the malopolskie province from the Austrian partition, and the swietokrzyskie province from the Russian partition. The subject of the evaluation of the changes in the agrarian structure is based on the comparisons made for the years 1921 and 2002. The Gini coefficient and the arable coefficient were applied in the analysis of the agrarian structure. As shown in the paper, despite the flow of many years, the transformations determining it, the changes in the agrarian structure within the three annexed areas were much alike. That means that in the provinces examined the agrarian structure is strongly conditioned by history. The differences in the agrarian structure between the three annexed territories have been maintained to date, despite the common agricultural and economic policies conducted within the area of Poland for almost 100 years.
Keywords: Q15; Q18; 330; agrarian structure; Gini coefficient; arable coefficient